Advancing offshore pipeline safety: Exploring non-invasive Electrical Resistance Tomography for upstream leak response detection Strategy - Muhammad Saad Khan (21993462) (2025)
This work investigates the use of Electrical Resistance Tomography (ERT) for early leak detection in multiphase flow pipelines considering the upstream leaks part (ERT situated before leaks), which tests traditional approaches in dynamic and heterogeneous environments. Experiments with Newtonian (water) and non-Newtonian (0.1 wt % Flozwan) fluids are conducted to explore initially flow regime identification followed by leak-induced fluctuations of air volume fractions under various flow conditions. Three simultaneous chronic leaks—measuring 3, 2.5, and 1.8 mm—in the middle region of a horizontal pipeline. The results showed that ERT could successfully follow dynamic changes of flow behavior in upstream leaks even when it was before the leak and distant from the leak source. The tests revealed that Newtonian fluids allow for greater air dispersion and leak sensitivity in terms of uniform viscosity and turbulence, whereas non-Newtonian fluids allow for less air dispersion and muted system responses due to shear-thinning behavior. These findings emphasize the necessity of fluid rheology for ERT sensitivity while also presenting the technology as a non-invasive, real-time diagnostic methodology for assuring pipeline safety and efficiency. Other Information Published in: Flow Measurement and Instrumentation License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.2139/ssrn.5142424